Role of Whole-Body Computed Tomography Scan to Avoid Missed Foreign Body in Patients with Multiple Stab Injury: A Rare Case of Retained Impaled Knife Blade with Intact Neurology - Hajare, Swapnil; Shetty, Ajoy; Ramachandran, Karthik; Shanmuganathan, Rajasekaran (Asian Journal of Neurosurgery, 2022)
Nonmissile penetrating spine injury (NMPSI) is usually encountered in young men, secondary to knife-inflicted injuries. Such injuries often present with complete or incomplete neurodeficit. We hereby report a case of NMPSI (due to impaled knife blade) in the cervical spine, who presented with intact neurology. She was managed by foreign body removal, dural repair, and cerebrospinal fluid (CSF) diversion with lumbar drain. We performed postoperative magnetic resonance imaging with diffusion tensor imaging and tractography to ascertain the cord status. The case highlights the importance of whole-body computed tomography in patients with multiple stab wounds and the use of CSF diversion in such situations.
Keywords: impaled knife; penetrating spine injury; whole-body CT scan